Factors Affecting Eye Drops Non-adherence in Patients with Glaucoma in Hua-Hin hospital - Guysorn, Nualnang (Hua Hin Medical Journal, 2025)
Background: Glaucoma is a progressive optic neuropathy and the leading cause of irreversible blindness worldwide. Effective medical treatment can prevent visual loss. Objective: To study the factors affecting eye drop non-adherence and the characteristics of non-adherence in glaucoma patients at Hua Hin Hospital. Methods: This study is a cross-sectional analytical study involving 172 glaucoma patients. Data were collected using a personal information and glaucoma medication usage questionnaire, along with a record of visual acuity and visual field data. Descriptive statistics were used to analyze general information, while multivariable logistic regression was employed to analyze factors affecting eye drop non-adherence. Results: The sample consisted of 51.2% male patients with an average age of 66.97 years. About 50.58% had been using glaucoma eye drops for 1-3 years, and 78.49% used two or more drops per eye per day. Regarding glaucoma staging, 61.05% were classified as having severe glaucoma, and visual acuity, 72.67% had normal to mild visual loss. The analysis of factors affecting eye drop non-adherence revealed that patients with blindness had 2.58 times higher odds of non-adherence (ORadj =2.58, 95%CI: 1.05-5.53) compared to those with better visual acuity. Additionally, patients under 60 years of age had 2.42 times higher odds of forgetting to use their eye drops (ORadj =2.42, 95%CI: 1.06-1.27) compared to those aged 60 and above. As for the characteristics of non-adherence, 61.2% of patients forgot to take their medication, 16.3% ran out of medication before their next scheduled refill, and only 1% of patients discontinued the medication on their own. Conclusion: Patients with blindness were more likely to be non-adherent to eye drop medication compared to those with better visual acuity. Additionally, patients under 60 years of age had a higher chance to forget to use their eye drops. Forgetting to use the eye drops was a common reason for non-adherence among glaucoma patients.